Effects of colchicine treatment on morphological variations of Neolamarckia cadamba - Eng, W.H.; Ho, W.S.; Ling, K.H. (2021)
This study described the effects of colchicine application on the morphological characteristics of Neolamarckia cadamba plantlets. Surface-sterilised seeds and in vitro-grown nodal segments were treated with different concentrations of colchicine (0.1%, 0.3%, and 0.5%) and durations (24 h and 48 h). For both seeds and nodal segment explants, mortality rates correlated positively with colchicine concentration and treatment duration. In terms of morphological characteristics, the explants showed a decrease in shoot length, but an increase in the percentage of shoots with abnormal leaves and darker green leaves over the control when treated with more severe colchicine. For seeds treated with colchicine, multiple shoot seedlings were also observed. The number of shoots proliferated correlated positively with the severity of colchicine treatment. It showed that colchicine could exert plant development in vitro, which is similar to plant growth regulators. The stem diameter of seedlings was larger when seeds were treated with colchicine. A higher colchicine concentration with a longer period of treatment of explants induced higher variation. The various morphological characteristics observed in the treated explants indicated genetic changes which could be useful for the genetic improvement of N. cadamba.